Splenic volume as a predictor of survival in cancer patients treated with immune checkpoint inhibitors - Zhang, Yunhua; Fu, Xin; Zhang, Lilong; Zhou, Qing; Wang, Weixing (Frontiers in Immunology, 2025)
ObjectiveThis investigation seeks to examine the association between spleen volume and prognosis in cancer patients undergoing immune checkpoint inhibitor (ICI) treatment.MethodsWe performed a retrospective analysis involving 61 patients diagnosed with hepatocellular carcinoma (HCC) who received ICIs at our institution. We evaluated the relationship between baseline splenic volume and its changes during ICI therapy concerning overall survival (OS) and progression-free survival (PFS) using a log-rank test. To identify relevant literature, we searched databases such as PubMed, EMBASE, the Cochrane Library, and Google Scholar up until February 20, 2024. The primary metrics assessed were hazard ratios (HR) for both OS and PFS, with pooled estimates and corresponding 95% confidence intervals (CIs) calculated.ResultsWithin our study population, findings demonstrated a significantly decreased OS (HR: 2.02, 95% CI: 1.08–3.77, p = 0.027) and PFS (HR: 1.84, 95% CI: 1.05–3.21, p = 0.032) in HCC patients with a high baseline spleen volume, compared to individuals with lower spleen volumes. Additionally, HCC patients who experienced an increase in spleen volume during ICI therapy exhibited significantly poorer OS (HR: 2.27, 95% CI: 1.17–4.41, p = 0.016) and PFS (HR: 2.40, 95% CI: 1.30–4.41, p = 0.005) than those whose spleen volume decreased. The meta-analysis results revealed that subjects with higher spleen volumes had a significantly reduced OS (HR: 1.74, 95% CI: 1.12–2.72, p = 0.014) and PFS (HR: 1.35, 95% CI: 1.15–1.58, p < 0.001) compared to counterparts with lower volumes. Furthermore, the data clearly highlighted that patients with increases in splenic volume faced significantly poorer clinical outcomes, as indicated by reduced OS (HR: 1.83, 95% CI: 1.36–2.46, p < 0.001) and PFS (HR: 1.70, 95% CI: 1.28–2.25, p < 0.001) relative to those with decreases in splenic size.ConclusionA higher baseline spleen volume and an increase in spleen volume during ICI therapy were predictors of a poor prognosis in cancer patients treated with ICI.